Analysis of load balance performance of multipath in wireless ad hoc networks - WANG Hui; YU Neng-hai (Tongxin xuebao)
A novel analysis model for computing the load of wireless ad hoc network that uses multipath routing was proposed. This model took the number of paths, the way of route selecting and the density of the network nodes into account and could analyse or compute the load in different network conditions. The result of the simulation fits the theory perfectly and give the conclusion that using multipath routing alone in wireless ad hoc network can not balance the load of network effectively. This is not the same as we always accept （using multipath routing in wireless ad hoc network can balance the load of network and increase throughput just as in the normal network）.